Tinjauan Hukum Terhadap Upaya Perlindungan Bagi Pekerja Migran yang Menjadi Korban Perdagangan Orang (Studi Kasus Perkara Nomor 587/Pid.Sus/2023/Pn.Pdg) - Reyza Darfebryanto; Sry Wahyuni (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
Indonesia's entry into the era of globalization has had a significant impact on various sectors of life, including the increased mobility of labor across countries. Behind this progress lies a serious issue in the form of human trafficking (TPPO), particularly through the illegal placement of migrant workers. Human trafficking is a violation of human rights involving the systematic and organized exploitation of individuals. TPPO is often carried out through illegal placement of migrant workers, with recruitment methods involving persuasion and promises of high-paying jobs abroad, which ultimately lead to labor exploitation, violence, and violations of individual freedom. A concrete example that becomes the focus of this research is Case Number 587/Pid.Sus/2023/PN Pdg, in which the victim was recruited and sent to Malaysia non-procedurally by the perpetrator using the modus operandi of promising a high-paying job.The research addresses the following problems:(1) What forms of legal protection exist for migrant workers who become victims of human trafficking according to existing laws and regulations?(2) What legal efforts can be made to ensure the protection of the rights of victims in the case of the placement of Indonesian migrant workers, as illustrated in Case 587/Pid.Sus/2023/PN Pdg?The research method used is normative juridical and case study, with data collection techniques through literature review of laws and regulations, legal literature, and court decision documentation.The results of this study show that human trafficking of Indonesian migrant workers requires serious attention from the government and society. There is a need to strengthen the legal framework, increase public awareness, and provide better protection for victims to prevent future TPPO cases. It is necessary to improve regulations and more effective legal implementation, as well as international cooperation to enhance the protection of Indonesian migrant workers This research aims to examine the legal protection of TPPO victims in the context of migrant worker placement, and to assess the effectiveness of the implementation of Law Number 21 of 2007 and Law Number 18 of 2017.The conclusion of this research indicates that legal protection for Indonesian Migrant Workers (PMI), particularly those who are victims of human trafficking (TPPO), has been regulated through various national and international regulations. However, despite the existence of strong regulations, the implementation of legal protection still faces numerous challenges in the field. Some of the main issues include weak coordination among related institutions, limited access for PMI to information and legal assistance, and the practice of illegal placement of PMI that makes them vulnerable to becoming TPPO victims.Illegal placement that does not follow procedures often opens the door to exploitation, particularly in the form of violence, slavery, or forced labor. Therefore, a more responsive and integrated legal approach among institutions is needed to ensure justice and recovery for TPPO victims.